MrgprB4 in trigeminal neurons expressing TRPA1 modulates unpleasant sensations - Shota Tobori; Haruka Hiyama; Takahito Miyake; Yuichi Yano; Kazuki Nagayasu; Hisashi Shirakawa; Takayuki Nakagawa; Yasuo Mori; Shuji Kaneko (Elsevier, 2021)
Gentle touch such as stroking of the skin produces a pleasant feeling, which is detected by a rare subset of sensory neurons that express Mas-related G protein-coupled receptor B4 (MrgprB4) in mice. We examined small populations of MrgprB4-positive neurons in the trigeminal ganglion and the dorsal root ganglion, and most of these were sensitive to transient receptor potential ankyrin 1 (TRPA1) agonist but not TRPV1, TRPM8, or TRPV4 agonists. Deficiency of MrgprB4 did not affect noxious pain or itch behaviors in the hairless plantar and hairy cheek. Although behavior related to acetone-induced cold sensing in the hind paw was not changed, unpleasant sensory behaviors in response to acetone application or sucrose splash to the cheek were significantly enhanced in Mrgprb4-knockout mice as well as in TRPA1-knockout mice. These results suggest that MrgprB4 in the trigeminal neurons produces pleasant sensations in cooperation with TRPA1, rather than noxious or cold sensations. Pleasant sensations may modulate unpleasant sensations on the cheek via MrgprB4.